Manfaat dan Mafsadat Teknologi Komunikasi terhadap Perkawinan menurut Hukum Islam - Mirdina Ayanah; Zul Mulki; Abd Rahman R; Kurniati Kurniati (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this research is to find out the benefits and meanings of communication technology for marriage according to Islamic law. The research method uses normative juridical research, namely library law research which is carried out by studying library materials or secondary data. The results of this study note that the benefits of communication technology for marriage according to Islamic law are (a) as a means to establish human relations, both friendly relations between relatives, relations with fellow friends, or work relations, (b) as a means of communication that can be used to improve the quality of relationships and harmony between family members/spouses and (c) facilitate the transfer of knowledge within a family. The meaning of communication technology for marriage according to Islamic law is to limit the personal sphere to blur, reduce interaction between families, waste time in vain and make partners jealous.